Pengaruh Literasi Keuangan, Penggunaan Digital Payment, dan Pendapatan terhadap Inklusi Keuangan di DKI Jakarta - Siti Aisyah Amini; Harya Kuncara Wiralaga; Karuniana Dianta Arfiando Sebayang (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to analyze the influence of financial literacy, digital payment usage, and income on financial inclusion in DKI Jakarta. This study uses a quantitative approach with a survey method through questionnaires distributed to 157 respondents who are digital payment users aged 15-59 years, have an income, and reside in DKI Jakarta. The analysis results show that financial literacy, digital payment usage, and income each have a positive and significant impact on financial inclusion. The R² value of 0.588 indicates that 58.8% of the variation in financial inclusion can be explained by the variables of financial literacy, digital payment usage, and income. Meanwhile, the remaining 41.2% is explained by other factors not discussed in this study.